Onomástica em ParkatêJê: um estudo morfossintático e semântico sobre os nomes próprios - LOPES, Tereza Tayná Coutinho (Universidade Federal do Pará, 2018)
This work aims at introducing linguistic and cultural issues related to the onomastic system from Parkatêjê people, also known in specialized literature as Gavião do Pará. Currently, the referred people live in villages at the Indian reserve Mãe Maria (RIMM), in the surroundings of Marabá town. The Parkatêjê language, named as its own community, belongs to the Complexo Dialetal Timbira, Macro-jê stock and, such as it is common to the Timbira people, it displays elaborated systems of nomination. The study of the proper names from different typologies is the central interest of the discipline named Onomastic, being anthroponymy, in other words, the study of personal proper names, the field of Onomastics is the focus of this work. Initially, after some general considerations about the Parkatêjê people, this work carried out a review of the studies on onomastics based on the perspective of authors like Dick (1996; 1997; 1999; 2000; 2001), Lyons (1977), Ullmann (1964), Seabra (2006), Carvalhinhos (2007), among others. Then, it was introduced a general overview about the nomination system of Timbira languages, based mainly on Coelho de Souza (2002), Nimuendajú (1946), Melatti (1938), Arnaud (1964) e Carneiro de Cunha (1986). Therefore, it was exhibited several morphosyntactic and semantic aspects verified in proper names of the Parkatêjê language. In regard to the morphosyntactic characteristics the works from Araújo (1989), Ferreira (2003), Booij (2007) and Diniz (2010) they were the main theoretical subsidies, while in concern of the semantic issues it was utilized assumptions of the Cultural Semantics and Cognitive Semantics to undertake the analysis carried out which are unpublished in the present dissertation. The Methodology used throughout this work was made through bibliography research, moreover of ethnographic research with data assortment carried out on the languages‘ community in study.